Molecular Biomarkers and Pathophysiology Specific to Bipolar Disorder - Salim, Megan Angelita; Abriana, Felicia Michelle; Tirta, Matthew Aurelius; Sanny, Sanny; Kristiani, Lidya (Indonesia International Institute for Life Sciences, 2023)
Bipolar disorder (BD) is an episodic neuropsychiatric disorder with fluctuations between manic and depressive phases according to their types (BDI/BDII/cyclothymic), contributing to the decreased quality of life due to the impairment of cognitive abilities. Early detection is needed for proper treatment, however, the gold standard Structured Clinical Interview for DSM-IV results in misdiagnosis due to its inability to distinguish BD from other neuropsychiatric disorders. Therefore, diagnosis through molecular biomarkers can be performed to accurately distinguish BD from other neuropsychiatric disorders. This review aims to elaborate the evidence of molecular biomarkers in BD patients from recent studies, which may be fundamental in clinical practices for accurate diagnosis. Proteomic studies provide evidence for the differentially expressed proteins, namely brain-derived neurotrophic factors, which can differentiate BD from major depressive disorder and schizophrenia. Moreover, genetic alterations from genomic and transcriptomic studies found that CACNA1C, ANK3, FADS2, and other genes may predispose an individual to BD. Some of these genes are closely related to BD pathophysiology occurrence, including impaired oxidative phosphorylation, imbalance in calcium homeostasis, and neuroinflammation, all of which arise due to mitochondrial dysfunction. These pathophysiology can be alleviated by proper administration of mood stabilizers, antipsychotics, and anticonvulsants, but novel treatments targeting specific pathophysiology and biomarkers of BD are required for better treatment effectiveness. Keywords: Bipolar disorder; mania/depression; molecular biomarker; mitochondrial dysfunction; pharmacotherapies